2022
DOI: 10.1097/md.0000000000032211
|View full text |Cite
|
Sign up to set email alerts
|

Anterior chamber parameters in cataract surgery candidates from middle China

Abstract: To determine the distribution of the anterior chamber parameters and associated factors in cataractous adults from middle China. In this cross-sectional study, axial length, anterior chamber depth (ACD) and lens thickness (LT) were measured with IOLMaster 700. The Pentacam HR was designed to measure the anterior chamber volume (ACV) and anterior chamber angle (ACA). Patients’ data were collected and analyzed between 2020 and 2022. A total of 157 eyes of 157 Chinese adults (mean age: 64.43 ± 12.16 years) with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Studies [17,33] have found a decrease in vault of approximately 5 μm per year, making age a protective factor for high vault. ACV narrowing or LT thickening can cause low vault in one direction, implying that both are more common (e.g., glaucoma, cataract, and diabetes) [34,35], and have a greater impact on posterior chamber structure [36]. Posterior chamber structure, one of the most important factors affecting vault [21], reverse compression of the iris concave surface can result in a reduced vault (< 100 μm) [19]; a small posterior chamber angle can restrict ICL contact with the deep surface of the ciliary sulcus and result in a high vault.…”
Section: Possibility Analysis Of Results Generationmentioning
confidence: 99%
“…Studies [17,33] have found a decrease in vault of approximately 5 μm per year, making age a protective factor for high vault. ACV narrowing or LT thickening can cause low vault in one direction, implying that both are more common (e.g., glaucoma, cataract, and diabetes) [34,35], and have a greater impact on posterior chamber structure [36]. Posterior chamber structure, one of the most important factors affecting vault [21], reverse compression of the iris concave surface can result in a reduced vault (< 100 μm) [19]; a small posterior chamber angle can restrict ICL contact with the deep surface of the ciliary sulcus and result in a high vault.…”
Section: Possibility Analysis Of Results Generationmentioning
confidence: 99%